Eliminace ztrát na ohraňovacích lisech - Kubový, Tadeáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Tato diplomová práce se zabývá návrhem na eliminaci ztrát na ohraňovacích lisech a celkovému zlepšení a optimalizaci procesu ohraňování. Návrhová část práce obsahuje dva návrhy, oba s cílem eliminovat ztráty a zvýšit výkon ohraňovací dílny. Práce je rozdělena na šest hlavních částí od teoretických východisek, přes analýzu celého výrobního procesu, detailní analýzu procesu ohýbání, až po návrh řešení a jeho zhodnocení.

This diploma thesis deals with a proposal for the elimination of losses on press brakes and the overall improvement and optimization of the press brake process. The design part of the work contains two proposals, both with the aim of eliminating losses and increasing the performance of the press break workshop. The work is divided into six main parts from the theoretical starting points, through the analysis of the entire production process, detailed analysis of the bending process, to the design of the solution and its evaluation.
Waste Elimination on Press Brakes
Keywords: proces; výroba; ohraňovací lis; analýza; chronometráž; layout; eliminace ztrát; optimalizace; štíhlá výroba; kaizen; process; production; press break; analysis; timing; layout; loss elimination; optimalization; lean manufacturing; kaizen